IMF Survey : Volume 28, Issue 14. (IMF Survey; IMF Survey ;, 1999)
Alassane D. Ouattara, a Cote d'lvoire national, is resigning as Deputy Managing Director of the IMF, a position he has held since July 1994. He was Director of the IMF's African Department from 1984 to 1988 (and was appointed a Counsellor of the IMF in 1987), Governor of the Banque Central des Etats de l'Afrique de l'Ouest from 1988 to 1990, and Prime Minister of Cote d'lvoire from 1990 to 1993. Ouattara spoke with Laura Wallace of the IMF's External Relations Department about the world economy, debt relief, conflict prevention, social issues, and the IMF's changing role.